(untitled) (Altre Modernità, 2020)
Since the 19th century, along with the expansion of the capitalist system, we see a growing attention to industrial waste as well as an increasing interest for the refuses of history. The recovery of these fragments, left aside from the official narration, represents the condemnation of a selection system which has often been an instrument of power and oppression. Thanks to the developing awareness of this mechanism, art takes on the task of exhuming and enhancing those waste materials through an archaeological perspective. The chiffonier, characterized by this archaeological vocation, is an emblematic figure of Paris during the Second Empire and a collector of the fragments of history. The main characters of Homer & Langley by Doctorow and Raymond Isidore e la sua cattedrale by Franzosini are contemporary chiffonniers who, through their works, create a monument to the objects of waste, while these biographical fictions rehabilitate the narration of these “wasted lives” dominated by mental alienation